Electrochemical reduction of disperse orange 1 textile dye at a boron-doped diamond electrode - Uliana, Carolina V. [UNESP]; Garbellini, Gustavo S. [UNESP]; Yamanaka, Hideko [UNESP] (Springer, 2012)
Electrochemical reduction of the azo dye disperse orange 1 (DO1) was performed by square wave and cyclic voltammetry using a boron-doped diamond electrode. The dissolution of DO1 was evaluated by monitoring the UV-Vis spectra of the solutions, and best results were obtained using aqueous solutions containing 5 % Fongranal FB dispersant. Three irreversible peaks were obtained for the electrochemical reduction of DO1, while the dispersant showed one irreversible peak. The overall electrodic process was mainly diffusion controlled. A mechanism is proposed for the reduction of the dye.
Keywords: Azo dyes; Dispersants; Diamond electrodes; Aromatic amines